(untitled) (Prilozi za književnost, jezik, istoriju i folklor, 2023)
In this article, we publish correspondence from Danica Pinterović addressed to the distinguished professor Filaret Granić. This correspondence contains one letter and one postcard from Danica Pinterović. It includes interesting data from her personal life as well as scientific activities. This correspondence provides an interesting contribution to the biography of F. Granić and Pinterović. Publishing this correspondence is a small contribution to the development of our Byzantinology.